Correction: Insulin resistance enhances the mitogen-activated protein kinase signaling pathway in ovarian granulosa cells. - Linghui Kong; Qien Wang; Jiewen Jin; Zou Xiang; Taoyu Chen; Shanmei Shen; Hongwei Wang; Qian Gao; Yong Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0188029.].